Protection of intestinal immune barrier against ischemia/reperfusion injury in a swine model using anisodamine hydrobromide - Guijuan Dong; Jun Yang; Xin Zhao; Shubin Guo (Universidade de São Paulo, 2022)
Abstract Intestinal ischemia/reperfusion (I/R) causes barrier impairment and bacterial influx. This study explored the protective effects of anisodamine hydrobromide (AH) on intestinal I/R injury caused by cardiopulmonary resuscitation (CPR) after cardiac arrest (CA). After successful CPR, minipigs were randomly divided into two groups (n = 8): saline and AH (4 mg/kg), and then treated with saline or AH via central venous injection, respectively. The same procedures without ventricular fibrillation initiation were conducted in the Sham group (n = 8). Levels of interferon gamma (IFN-γ) and interleukin 4 (IL-4) were measured at different time points (0, 0.5, 1, 2, 4, and 6 h) in serum and 6 h in gut associated lymphoid tissues (GALTs) after the return of spontaneous circulation (ROSC) to evaluate changes in the proportion of T-helper type 1 (Th1) and T-helper type 2 (Th2). Moreover, the positive culture rates of GALTs were examined to evaluate bacterial translocation. AH treatment markedly alleviated aberrant arterial blood gas and hemodynamics as well as intestinal macroscopic and morphological changes after CPR. Moreover, AH treatment significantly increased IFN-γ and decreased IL-4 in both serum and GALTs. Furthermore, AH treatment dramatically decreased positive bacterial growth in GALTs. AH treatment mitigated immunosuppression caused by intestinal I/R and protected the intestinal immune barrier against bacterial translocation, thereby reducing the risk of secondary intestinal infection.